The Role Of Arab Logicians In The Development Of Linguistic Research: Singular Noun As An Example - et. al., Mohammed Amer Mohammed, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper deals with a unique definition of the visa, but it can be used either to refer to one specific meaning, such as knowledge, or to denote a multiple meaning, such as common, transmitted, partner, skeptical, truth and metaphor, with the difference between the statement of these connotations and the problems that it may respond to. . Let us conclude that the region played a major role in the development of linguistic research.